4m-18=-2+-6

Simple and best practice solution for 4m-18=-2+-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m-18=-2+-6 equation:


Simplifying
4m + -18 = -2 + -6

Reorder the terms:
-18 + 4m = -2 + -6

Combine like terms: -2 + -6 = -8
-18 + 4m = -8

Solving
-18 + 4m = -8

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 4m = -8 + 18

Combine like terms: -18 + 18 = 0
0 + 4m = -8 + 18
4m = -8 + 18

Combine like terms: -8 + 18 = 10
4m = 10

Divide each side by '4'.
m = 2.5

Simplifying
m = 2.5

See similar equations:

| =20x+180 | | (3ad^4)(-2a^2)= | | 6x^(-2/3)-13x(-1/3)-5=0 | | y=-3/5x-3 | | 5x+9-x=134 | | 2x-72+90=180 | | 8x^2=64x*lg(x) | | 9x-8=6+x^2 | | x^2+18x-0=0 | | 12+-X-4.5=-14 | | 12j+15=-13j-35 | | 12-X-4.5=14 | | -24=8-4K | | 6x+36+90=180 | | x^3-6x^2+12x+4=0 | | 3x^2-6x+3y-7=0 | | -15x-20=-13+110 | | m=(25-x)/(21-48.28) | | 2(x+10)=3(4-x) | | M^2-7m-13=-10 | | 0=-1.25t^2+21.25t | | 1.3772=19.4645x+1.3739 | | 12x-20=-10x+110 | | 4b^2+8b+7=42 | | 1.3772=9E-05x+1.3739 | | 1.3372=9E-05x+1.3739 | | ln(x/(x^2-4)) | | 500x+300y=103.57 | | 3x+4(x-1)=2.5 | | 90+32+8x+34=180 | | 7x/10=2=16 | | Y-50/6=6 |

Equations solver categories